1993
DOI: 10.3109/03639049309050174
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Quality of Glibenclamide Products A Multinational Postmarket Comparative Study

Abstract: A multinational postmarket comparative study of pharmaceutical quality of glibenclamide products was performed in cooperation with large number of laboratories and under anspices of the Section of Official Laboratories and Medicines Control Services of FIP and World Health Organization. 28 countries from Europe, Africa, North and South America, Asia and Australia participated in this study. Altogether 142 glibenclamide tablet formulations of the respective countries were investigated. The products were tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 1 publication
1
18
0
1
Order By: Relevance
“…The study hypothesis was that the different drug products would meet the criteria for in vitro equivalence. The dissolution studies presented in this report repeat the type of studies conducted by Blume et al with the difference that BCS criteria were incorporated into the study design (14)(15)(16). With the understanding arising from the BCS, the studies in the present report can also signal bioequivalence, which is termed in vitro equivalence where applicable.…”
Section: Introductionmentioning
confidence: 52%
“…The study hypothesis was that the different drug products would meet the criteria for in vitro equivalence. The dissolution studies presented in this report repeat the type of studies conducted by Blume et al with the difference that BCS criteria were incorporated into the study design (14)(15)(16). With the understanding arising from the BCS, the studies in the present report can also signal bioequivalence, which is termed in vitro equivalence where applicable.…”
Section: Introductionmentioning
confidence: 52%
“…The poor water solubility of GLY is responsible for its poor dissolution rate, which ultimately leads to variable absorption of GLY. Furthermore, there are reports which have documented that GLY shows large variations in interindividual bioavailability and bioequivalence of the marketed products (3,4). Thus, it can be concluded that the bioavailability and in vivo performance of GLY is dependent on its dissolution rate.…”
Section: Introductionmentioning
confidence: 99%
“…Растворимость глибенкламида в желудочном соке и pH в желудочно-кишечном тракте влияют на всасывание препарата [11]. Срав-нительные постмаркетинговые исследования гли-бенкламида продемонстрировали вариации в био-доступности и зависимость адсорбции при перо-ральном приеме от лекарственной формы [13]. Для повышения растворимости и биодоступности гли-бенкламида применялись различные подходы, ко-торые включали добавление сурфактантов, образо-вание комплексов с циклодекстринами, приготов-ление твердых дисперсионных систем, микрониза-ция и преобразование кристаллической решетки соединения [11,14].…”
Section: микронизированная форма глибенкламидаunclassified